Maltrato de tipo físico, psicológico, emocional, sexual y económico en el noviazgo: un estudio exploratorio (2009)
This exploratory study examined the prevalence of 68 forms of physical, psychological, emotional, sexual and economic partner maltreatment and the correlation between the duration of the relationship and the general frequency of the abuse in a sample of 403 single Colombian adolescents and adult youths, 149 males and 254 females, 15-30 years-old. Results showed that 82.6% (n=333) informed of having been object, at least once, of some type of abusive partner conduct. There were not significant differences by gender in the general prevalence neither by type of abuse, except for the economic maltreatment, where the prevalence was higher for males. There was also a statistically-significant positive correlation between the duration of the relationship and the general frequency of the abuse, specifically physical and psychological.